BIOCHEMICAL CHARACTERISATION OF MUSCOVY AND MALLARD DUCKS IN NIGERIA (2014)
Protein polymorphism and alleleic variation were investigated in the blood and egg proteins of the Muscovy and Mallard duck breeds found in Southwestern Nigeria. Four proteins namely haemoglobin, transferrin, carbonic anhydrase, and albumin in the blood and two egg white proteins:ovalbumin and conalbumin were analysed .A total of 50 ducks comprising of 30 Mallard duck and 20 Muscovy ducks and 20 eggs from each breed were used for the analysis. Separation of blood and egg protein genotypes was achieved using cellulose acetate electrophoresis. Two co-dominant allele A and B controlling three genotypes AA, AB and BB were observed at haemoglobin, transferrin and carbonic anhydrase loci investigated for both breeds. A third allele C was observed at the albumin locus in the Mallard breed. . Allele A was the most predominant at the Hb, Tf and CA locus in the Muscovy breed with frequencies 0.775, 0.575, and 0.675 respectively and in the Mallard at the Tf, CA and Al locus with frequencies 0.667, 0.567 and 0.767 respectively. The frequencies of allele A and B at the conalbumin locus were 0.425, 0.575; 0.525, 0.475 in the Muscovy breed. Estimates of heterozygosity were 0.428 and 0.430 in the Muscovy and Mallard ducks respectively. Dendogram generated from the genetic distance values revealed that the two breeds are closely related. High genetic similarity was observed between the two breeds.